السياسة الجبائية ودورها في تحقيق التنمية المحلية دراسة حالة – بلدية الوادي 2009/2015 - بحري, لحسين (جامعة الوادي -University eloued, 2017)
تعد السياسة الجبائية من بين أهم السياسات العامة التي تستخدمها الدولة، كأداة فعالة لتمويل التنمية المحلية بأبعادها المختلفة، خاصة بعد تطور دور الدولة من دولة حارسة ذات مهام محددة، إلى دولة متدخلة في النشاط الاقتصادي ، تماشيا مع التغيرات التي تشهدها الساحة الدولية في شتى المجالات الاقتصادية والسياسة والاجتماعية. وفي هذا الإطار سعت الجزائر إلى تجسيد نظام الجماعات المحلية، وجعلها أداة أساسية لتحقيق التنمية المحلية، باعتبارها الأقرب إلى معرفة الحاجات المحلية، والأقدر على تجسيدها وتنفيذها، انطلاقا من المهام والصلاحيات التي أسندت لها، والذي يتطلب منها توفير موارد مالية تساعدها على تحقيق ذلك، ولهذا عملت الدولة الجزائرية على توفير مصادر تمويل هامة، تمكنها من القيام بعملية التنمية المحلية، ومن بينها نجد الجباية المحلية التي تمثل أهم مورد خصص لتمويلها، حيث نجد أن هناك أنواع عديدة من الضرائب التي تفرض من قبل الدولة على المواطنين، فمنها ما يعود كلية للجماعات المحلية، ومنها ما يعود بصفة جزئية، كما أن هناك ضرائب أخرى تشترك فيها الدولة، إذ يمثل هذا المورد من أهم الموارد التي تمول ميزانية الجماعات المحلية، إلا أنها تعتبر ضئيلة ولا تكفي لتغطية متطلبات المجتمع المحلي، الذى عمدت الدولة الجزائرية إلى إدخال إصلاحات مالية تتعلق بالجباية المحلية، ثم بلورتها في قوانين المالية المختلفة بهدف تمكين الجماعات المحلية من توفير موارد مالية كافية، من خلال مجموعة من الآليات والإجراءات القانونية التي تزيد من فعالية دورها التنموي، و الحد من مختلف العوائق التي تعترض طريقها. The fiscal policy is one of the most important public policies used by the state as an effective tool to finance local development in its various dimensions, especially after the development of the role of the state from a guarded state with specific tasks to a country that is involved in economic activity in line with the changes taking place in the international arena in various economic fields And social policy. In this context, Algeria sought to embody the system of local communities and to make them an essential tool for local development, as the closest to the knowledge of local needs and the best able to realize them and implement them from the tasks and powers entrusted to them. The Algerian state has provided important sources of funding to enable it to carry out the local development process, including the local tax collection, which represents the most important source of funding. There are many types of taxes imposed by the state on citizens. Some of which are partly due, and other taxes are shared by the state. This is one of the most important resources that finance the budgets of the local communities, but it is considered small and insufficient to cover the requirements of the local community. Related to the local collection, and then crystallized in the various financial laws in order to enable the local communities to provide sufficient financial resources through a set of mechanisms and legal procedures that increase the effectiveness of their development role and reduce the various obstacles to their
ماستر سياسة عامة
Keywords: السياسة الجبائية، التنمية المحلية، التمويل المحلي، الجماعات المحلية، الجباية المحلية. الاستثمار المحلي.; Fiscal policy, local development, local finance, local communities, local tax collection. Domestic investment.